Якою має бути українська національна ідея? - Кіпенський, Андрій Володимирович; Перевалова, Людмила Вікторівна; Яценко, Ольга Миколаївна (НТУ "ХПІ", 2017)
У статті розглядаються підходи до розуміння національної ідеї, аналізуються різні точки зору учених, політиків на поняття національної ідеї, її формування в різних країнах світу. Автори звертають увагу на невизначеність параметрів національної ідеї, її співвідношення до державної ідеології, ролі еліт у формуванні національної ідеї. Досліджуються проблеми та перспективи формування національної ідеї в Україні, обґрунтовується змістовне наповнення національної ідеї. Розглядаються причини, що ускладнюють процес формування національної ідеї на сучасному етапі розвитку української держави.

The article deals with various approaches to understanding the national idea, analyzes different viewpoints of scientists and politicians on the notion of the national idea, its formation in different countries of the world. The authors draw attention to uncertainty of the parameters of the national idea, its correlation with the state ideology, the role of elites in the formation of the national idea. The problems and prospects of the formation of the national idea in Ukraine are studied; the content of the national idea is grounded. The reasons that complicate the process of forming the national idea at the present stage of the Ukrainian state development are discussed.
What should the Ukrainian national idea be?
Keywords: ідеологія державна; народ; меншини національні; народ корінний; мова; релігія; state ideology; people; national minorities; native peoples; language; religion